Cooling Rates of Mahogany (Swietenia macrophylla King.) and Yemane (Gmelina arborea Roxb.) Determined by Infrared Thermography and Its Relationship to Density - Rana, Prince Ranier Cacaos; Marasigan, Oliver Segundo (Jurnal Sylva Lestari, 2026)
Determining wood density is essential for assessing its mechanical properties and industrial suitability, yet traditional methods are destructive and impractical for standing trees or finished products. This study investigates the application of infrared thermography (IRT) as a rapid, nondestructive method for estimating wood density from cooling behavior. Mahogany (Swietenia macrophylla King.) and yemane (Gmelina arborea Roxb.), two economically important plantation species in the Philippines, were examined under controlled heating and natural cooling conditions. Twelve samples with varying densities at 60°C were analyzed, and their cooling curves were modeled using the first-term transient plane-wall solution. A strong inverse correlation was found between density and cooling rate constant (kapp with coefficients of determination (R²) values of 0.90 for mahogany and 0.97 for yemane, confirming that denser samples cooled more slowly. Additionally, a 21% difference in cooling rates between mahogany and yemane at similar densities suggests that species-specific characteristics may influence heat loss. These results demonstrate the potential of IRT as a rapid, nondestructive tool for estimating wood density, with applications in timber grading, quality assessment, and forest resource monitoring; accordingly, this approach could be adapted for rapid on-site density estimation in timber grading and monitoring. Keywords: Gmelina arborea, infrared thermography, nondestructive testing, rate of cooling, Swietenia macrophylla